Perceptions and experiences of health care professionals and staff with animal-assisted interventions in health care settings: a qualitative systematic review protocol. Issue 3 (11th March 2022) - Beck, Amy J.; Barber, Tanya; McKenzie, Holly; Thorlakson, Jessica; Dell, Colleen; Keeping-Burke, Lisa
ABSTRACT: Objective: The objective of this review is to examine the perceptions and experiences of health care professionals and staff in implementing or coordinating animal-assisted interventions in health care settings. Introduction: Animal-assisted interventions are applied in the areas of health, education, and human services to help improve individuals' health and wellness. The positive effects of animal-assisted interventions on individuals have been shown in multiple health disciplines, from pediatrics to long-term care, and include outcomes such as decreased feelings of loneliness and increased feelings of support. The increase of animal-assisted interventions in human health has initiated growing research on health care professionals' perceptions and experiences of these interventions. No current qualitative systematic reviews have focused solely on health care professionals' and staff's perceptions of animal-assisted interventions. Conducting such a review will advance understanding of how these providers perceive and engage with animal-assisted interventions as well as their influence and role in coordinating these interventions. Inclusion criteria: This review will consider qualitative primary studies that address the perceptions and experiences of health care professionals and staff in implementing or coordinating animal-assisted interventions in health care settings. Methods: Nine bibliographic databases will be systematically searched for published and unpublished studies by employing a three-step search strategy. Studies published from database inception to present and in English will be considered. Two reviewers will independently appraise the studies and extract qualitative data using the standardized JBI critical appraisal and data extraction instruments. Findings from the review will be categorized according to similarity in meaning, and categories will be subjected to a meta-synthesis to produce a single comprehensive set of synthesized findings. Systematic review registration number: PROSPERO CRD42021258909